KESESUAIAN PENGGUNAAN KLAUSUL NEGATIVE PLEDGE OF ASSETS DALAM PERJANJIAN KREDIT OLEH BANK UMUM DENGAN PRINSIP KEHATI-HATIAN: TINJAUAN PERBANDINGAN HUKUM - Tjahjono, Monica; Sugianto, Fajar; Susantijo, Susi (Jurnal Hukum Magnum Opus, 2022)
Abstract This writing is intended to convey basic understanding of the application of the prudential principle in credit agreement that applied negative ledge of assets clause by commercial banks. The method is normative legal research with comparative legal system as the approach between Indonesia, Singapore and the Netherlands. The problem arises when the credit provided is in the form of large provision of funds which can be deemed as the form of syndicated loan. The collateral is set only for one holder and when set for more than one holder, it changes the creditors structure. Meanwhile, the distribution of assets for each creditors is not efficient. Therefore, to overcome this matter, a possible way of conducting credit agreement by the commercial banks is to apply the negative pledge of assets clause, which is, a clause which states that the debtor will waive his/her rights to pledge the assets to any other party. The result of the comparison is that there is a legal vacuum in Indonesia, while in Singapore and the Netherlands has been regulated the application of such clause as a means in conducting the 5 C’S principle. In the event of bankruptcy, the structure of the bank as one of the creditors will become concurrent and the collateral is debtor’s assets. Keywords:, comparative law; credit agreement; negative pledge of assets Abstrak Tulisan ini bertujuan untuk mengetahui penerapan prinsip kehati-hatian terhadap perjanjian kredit oleh bank umum yang menggunakan klausul negative pledge of assets. Metode yang digunakan ialah yuridis normatif dengan pendekatan perbandingan hukum antara Indonesia, Singapura, dan Belanda. Permasalahan muncul ketika kredit yang diberikan berupa penyediaan dana besar sehingga berbentuk kredit sindikasi. Jaminan kebendaan hanya diberikan untuk satu orang pemegang jaminan dan ketika diberikan untuk lebih dari satu orang akan menimbulkan peringkat. Sementara pembagian aset untuk masing-masing piutang kreditur tidaklah efisien. Oleh karenanya, untuk mengatasi hal ini, terdapat opsi untuk menggunakan klausul Negative Pledge of Assets, yakni klausul yang menyatakan bahwa debitor tidak akan menjaminkan satu atau sebagian dari aset-asetnya kepada pihak lain. Hasil perbandingan ialah terdapat kekosongan hukum di Indonesia, sementara di Singapura dan Belanda telah diatur dan menjadi bagian dari prinsip 5C. Dalam hal terjadi kepailitan, kedudukan kreditor akan menjadi kreditor konkuren dan jaminan yang digunakan ialah jaminan meliputi aset-aset debitor. Kata kunci: klausul negative pledge of assets; perbandingan hukum; perjanjian kredit